Fabrication and characterisation of MgO-based redox random access memory - Andhita Dananjaya, Putu (2015)
Emerging memory technologies must low in energy consumption, easily integrable into high density memory architecture, with high scalability, fast operating speed, high endurance capability, and long retention time. Due to this requirement, two terminal memory cells are getting more and more attention in recent years. Redox Random Access Memory is one of the most promising two terminal memory candi- date for the future memory technology. In this work, fabrication and characterisa- tion of Magnesium Oxide-based ReRAM device is extensively study. Magnesium oxide (MgO) has been one of the most preferred materials for MOS, MTJ, and spin valves applications. It has a considerably low formation of interfacial layers for deposition, a high thermal conductivity and breakdown field, large band gap, and a high dielectric constant, subject to the fabrication process. These proper- ties enhance the potential of MgO thin films to establish sufficient band offsets and to minimise the presences of leakage currents in device applications. Several studies have shown the potential of MgO in ReRAM application. However, the MgO-based ReRAM device has been known to have a considerably high operating voltage that lead to high energy consumption. In this study, the change subject to fabrication parameters such as post-deposition annealing and introduction of dopants are studied to enhance the performance of MgO-based ReRAM. Further- more, the dominant conduction mechanisms for the high and low resistance states of the device are investigated, which suggest a great possible improvement can be done in the scalability aspect of the device.